Intrinsic resolutions of DEPFET detector prototypes measured at beam tests - Andricek, Ladislav; Caride, J.; Doležal, Z.; Drásal, Z.; Esch, S.; Frey, A.; Furletova, J.; Furletov, S.; Geisler, C.; Heindl, S.; Iglesias, C.; Knopf, J.; et al. (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2011)
The paper is based on the data of the 2009 DEPFET beam test at CERN SPS. The beam test used beams of pions and electrons with energies between 40 and 120GeV, and the sensors tested were prototypes with thickness of 450μm and pixel pitch between 20 and 32μm. Intrinsic resolutions of the detectors are calculated by disentangling the contributions of measurement errors and multiple scattering in tracking residuals. Properties of the intrinsic resolution estimates and factors that influence them are discussed. For the DEPFET detectors in the beam test, the calculation yields intrinsic resolutions of ≈1μm, with a typical accuracy of 0.1μm. Bias scan, angle scan, and energy scan are used as example studies to show that the intrinsic resolutions are a useful tool in studies of detector properties. With sufficiently precise telescopes, detailed resolution maps can be constructed and used to study and optimize detector performance.